Lipoprotein-associated phospholipase A2 (Lp-PLA2): a key hub linking lipid metabolism and immune inflammation - Li, Dandan; Qian, Yuanbo; Wan, Li; Zhang, Kaixin; Song, Lifeng; Zhang, Xianjing; Yang, Xiaorong (Frontiers in Immunology, 2026)
Lipoprotein-associated phospholipase A2 (Lp-PLA2), also known as phospholipase A2 group VII (PLA2G7), is an enzyme that serves as a critical nexus between lipid metabolism and immune regulation. It exhibits dual and context-dependent functions by hydrolyzing platelet-activating factor (PAF) and oxidized low-density lipoprotein (oxLDL). The degradation of PAF results in the production of Lysoplatelet activating factor (LysoPAF), which attenuates inflammatory signaling. In contrast, the hydrolysis of oxLDL generates lysophosphatidylcholine (LysoPC) and oxidized fatty acids (oxFA), which exacerbate vascular inflammation, promote macrophage M1 polarization, and inhibit CD8+ T cell activity. Through these pathways, Lp-PLA2 is implicated in a range of diseases, including atherosclerosis, diabetes, Alzheimer’s disease, cancer, autoimmune disorders, and inflammation associated with infections. Despite extensive pharmacological interventions targeting this enzyme, clinical outcomes have been inconsistent, reflecting its complex roles across various pathophysiological contexts. This review synthesizes current knowledge on the mechanisms of Lp-PLA2, its associations with diseases, and its therapeutic implications, emphasizing its potential as both a biomarker and a therapeutic target at the intersection of lipid metabolism and immune response.